2012
DOI: 10.1002/ajmg.b.32046
|View full text |Cite|
|
Sign up to set email alerts
|

Association of CRHR1 and CRHR2 with major depressive disorder and panic disorder in a Japanese population

Abstract: Major depressive disorder (MDD) and panic disorder (PD) are common and disabling medical disorders with stress and genetic components. Dysregulation of the stress response of the hypothalamic-pituitary-adrenal axis, including the corticotrophin-releasing hormone (CRH) signaling via primary receptors (CRHR1 and CRHR2), is considered to play a major role for onset and recurrence in MDD and PD. To confirm the association of CRHR1 and CRHR2 with MDD and PD, we investigated 12 single nucleotide polymorphisms (SNPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 33 publications
1
37
1
Order By: Relevance
“…The CRH receptor 1 (CRHR1) triggers the release of the stress response regulating hormone cortisol. Preclinical and clinical studies have indicated that CRHR1 is a possible candidate gene for mood and anxiety disorders[79,125,126]. Weber et al[127] studied different variants located within the CRHR1 gene with regard to possible associations with PD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRH receptor 1 (CRHR1) triggers the release of the stress response regulating hormone cortisol. Preclinical and clinical studies have indicated that CRHR1 is a possible candidate gene for mood and anxiety disorders[79,125,126]. Weber et al[127] studied different variants located within the CRHR1 gene with regard to possible associations with PD.…”
Section: Resultsmentioning
confidence: 99%
“…CRH plays a central role in the regulation of the HPA axis. Preclinical and clinical studies have indicated that CRHR1 is a possible candidate gene for PD[125,126]. In a multi-level study by Weber et al[127], one allele was found to increase risk for PD in females.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cis-phase interaction between the SNPs within the EGF locus might contribute toward the etiology of MDD. Some other studies also found association of polymorphisms in corticotrophin-releasing hormone receptors 1 and 2 (CRHR1 and CRHR2) genes (Ishitobi et al, 2012) and the FK506-binding protein 5 (FKBP5) gene which regulate the hypothalamic-pituitary-adrenal axis (Kang et al, 2012) with vulnerability to MDD.…”
Section: Polymorphisms In Major Depressive Disordersmentioning
confidence: 94%
“…Polymorphisms and common haplotypes of the CRHR1 gene, encoding a CRH receptor, are associated with the risk of MDD, early age of onset of the first depressive episode, recurrence of MDD, and treatment response to antidepressants, including citalopram and fluoxetine [17][18][19][20]. Another CRH receptor, CRHR2, is also associated with MDD [21]. FK506-binding protein 5 7 with MDD via an interaction with SLEs [29].…”
Section: Introductionmentioning
confidence: 99%